Pengembangan E-LKPD Menggunakan Model Problem Based Learning Pada Materi Pecahan Kelas IV Sekolah Dasar - Novianto, Anwar; Yusuf, Anwar Sultan; Nisa, Nada Khoirun; Victriyani, Tyas; Puspitasari, Adhelia (Universitas Muhammadiyah Magelang, 2025)
This development research aims to produce a product in the form of an Electronic Student Worksheet (E-LKPD) based on the Problem-Based Learning (PBL) model by utilizing the Liveworksheet platform. The E-LKPD is expected to improve students’ understanding of fractions, specifically among fourth-grade elementary school students. The study was motivated by the low level of student comprehension in learning fraction material. The research method used is Design and Development (D&D), as developed by Richey and Klein, with the ADDIE development model, the study was conducted in the fourth grade of SD Negeri Gamping. Data collection instruments included expert validation sheets, teacher response questionnaires, and student response questionnaires. The results of this study are (1) Material expert validation obtained a percentage value of 87.5% (very decent). (2) Media expert validation obtained a percentage value of 81.8% (very decent). (3) Teacher response obtained a percentage value of 96.4% (very good). (4) Students response obtained a percentage value of 88.9% (veri good). (5) The average result of working on E-LKPD questions using the Liveworksheet website for students in groups is 86.7%. From the validation result, the the E-LKPD product is included in the “very decent” and “very good” criteria to be used as one of the supports in the technology-based learning process and interactive digital teaching materials in Mathematics subjects with fraction material. The development of E-LKPD based on PBL learning model is able to build students' enthusiasm through the presentation of challenging contextual problems, encourage active involvement during the learning process, support a deeper understanding of fraction concepts and strengthen students' readiness in facing learning challenges in the digital era.